If f(x) = 3x + 2 and g(x) = x2 + 1, which expression is equivalent to (f circle g) (x)? (3x + 2)(x 2 + 1) 3x 2 + 1 + 2

Question

If f(x) = 3x + 2 and g(x) = x2 + 1, which expression is equivalent to (f circle g) (x)?
(3x + 2)(x 2 + 1)
3x 2 + 1 + 2
(3x + 2)2 + 1
3(x 2 + 1) + 2

in progress 0
Genesis 2 months 2021-09-26T00:19:03+00:00 2 Answers 0 views 0

Answers ( )

    0
    2021-09-26T00:20:25+00:00

    Answer:

    (3x+2)^2+1

    Step-by-step explanation:

    (f°g)(x) =g(f(x)) =g(3x+2)=(3x+2)^2 +1

    0
    2021-09-26T00:20:46+00:00

    Answer:

    (3x + 2)2 + 1

    Step-by-step explanation:

Leave an answer

45:7+7-4:2-5:5*4+35:2 =? ( )